Peri-interventional Triple Therapy With Dabigatran Improves Vasomotion and Promotes Endothelialization in Porcine Coronary Stenting Model - Hemetsberger, Rayyan; Farhan, Serdar; Lukovic, Dominika; Zlabinger, Katrin; Hajagos-Toth, Judit; Bota, Judit; Garcia-Garcia, Hector M.; Ay, Cihan; Samaha, Eslam; Gaspar, Robert; Garamvölgyi, Rita; Huber, Kurt; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: We evaluated the short and long-term effect of peri-interventional dabigatran therapy on vasomotion, endothelialization, and neointimal formation in a porcine coronary artery stenting model. Background: Stenting of coronary arteries induces local inflammation, impairs vasomotion and delays endothelialization. Methods: Twenty-eight animals underwent percutaneous coronary intervention (PCI) with drug eluting stents. Sixteen pigs started dabigatran therapy 4 days prior to PCI and continued for 4 days post-stenting, while 12 animals served as controls. Post-stenting dual antiplatelet therapy (75 mg clopidogrel and 100 mg aspirin) was continued in both groups until termination. Immediately post-stenting and at day 3 optical coherence tomography (OCT) was performed in all animals, followed by euthanasia of 8 dabigatran and 4 control animals. The remaining pigs (8 of each group) were followed up for 1 month, with control angiography and OCT. Tissue burden (degree of peri-strut structure—thrombus and/or fibrin) was evaluated. After euthanasia coronary arteries were harvested for in-vitro myometry and histology. Results: Thrombin generation was lower (p < 0.001) and tissue burden (0.83 ± 0.98 vs. 3.0 ± 2.45; p = 0.031) was significantly decreased in dabigatran treated animals. After 3 days post-PCI endothelium-dependent vasodilation was significantly improved (77 ± 40% vs. 41 ± 31%, p = 0.02) in dabigatran animals. Neither quantitative angiography nor histomorphometry showed differences between the groups. Endothelialization was faster in the dabigatran group as compared with controls (p = 0.045). Conclusion: Short-term peri-interventional triple therapy with dabigatran, aspirin, and clopidogrel led to an enhanced endothelium dependent vasodilation and faster endothelialization. However, neointimal formation 1-month after stent implantation was comparable between groups.